Lecopelese - A novel evaluation model for measuring educational aspects of game-based learning - Al Fatta, Hanif; Maksom, Zulisman; Zakaria, Mohd Hafiz (Information Technology Department Politeknik Negeri Padang, 2025)
This study aimed to establish a model for assessing the pedagogical quality of mobile game-based learning (GBL), which seeks to convey educational content to users. Evaluating the educational effectiveness of GBL necessitates a robust model tailored for this purpose. Current models can be improved to better address various educational challenges associated with mobile GBL. The LECOPELESE (LEarning COntent, PEdagogy and LEarning StyLE) model was developed by integrating relevant constructs identified in existing literature. To validate this model, a qualitative research approach was employed, drawing a sample from 270 undergraduate students. The analysis utilized Structural Equation Modeling (SEM) and resulted in a final model based on rigorous factor analysis. The findings indicated that the proposed model effectively measures educational quality in game-based learning. This new model includes more comprehensive constructs and items, addressing the educational aspects of game-based learning. Specifically, the model introduces a pedagogy construct to evaluate game-based learning quality, reflecting criteria for outstanding educational content and delivery through mobile applications. It assesses how effectively GBL provides real-world learning experiences. Additionally, the research highlights that the quality of pedagogy is influenced by two key factors: the GBL's ability to accommodate learners' unique characteristics (learning styles) and the quality of the learning content that adapts to learners' needs. Ultimately, the study demonstrates that both learning content and style significantly impact the pedagogy construct, suggesting that enhancing these areas can improve the overall pedagogical quality of game-based learning.